Highly Conductive MXene Film Actuator Based on Moisture Gradients. (4th June 2020) - Wang, Jingfeng; Liu, Yuyan; Cheng, Zhongjun; Xie, Zhimin; Yin, Liang; Wang, Wu; Song, Yingbin; Zhang, Haiyang; Wang, Youshan; Fan, Zhimin
Abstract: MXene (Ti3 C2 T x ) is a new 2D material with both hydrophilicity and high electrical conductivity, and it has shown promise in smart electronic devices. Reported herein is a homogeneous MXene film actuator with high electrical conductivity triggered by moisture gradients. The actuator is highly sensitive to moisture and undergoes deformation, with the maximum bending angle as high as 155° at a relative humidity difference of 65 %. Several analysis methods show that the humidity drive and large deformation of the MXene film occur in situ by asymmetric expansion of the bilayer structure. The combination of deformation and electrical conductivity makes this film applicable to flexible excavators, electrical switches, and other fields, applications that are difficult to achieve directly by using other 2D materials. More importantly, this work further expands the new application range of MXene materials and provides new opportunities for building the next generation of high‐conductivity smart actuators. Abstract : Thin film : A homogeneous MXene film actuator with both hydrophilicity and high electrical conductivity was fabricated by a vacuum‐assisted filtration process. The film is highly moisture‐sensitive and can undergo a considerable amount of deformation. The high‐performance MXene film actuator makes it applicable to flexible excavators, electrical switches, and other fields, applications that are difficult to achieve by using other 2D materials directly.